Randomized controlled trial on the promotion of sexual health using "self-care interventional package" in men who have sex with men - Anjali Sharma; Karobi Das; Sushma Kumari Saini; Sandhya Ghai; Sandeep Mittal; Manmeet Kaur (Wolters Kluwer Medknow Publications, 2021)
Purpose: Men who have sex with men (MSM) is a vulnerable group, who have been neglected and discriminated. Such discrimination decreases their access to health care and increases the spread of sexually transmitted infections (STIs) and human immunodeficiency virus (HIV). Aims and Objective: The objective is to evaluate the effectiveness of "self-care interventional package" on the promotion of sexual health, among MSM. Materials and Methods: A randomized controlled trial was conducted on MSM from two nongovernmental organization centers of Chandigarh, which were randomized by simple random sampling into a control and experimental group. Over a period of 1 month, a total of 115 MSM were found eligible; 55 in control group and 60 in experimental group. Data were collected by a personal interview, after taking consent, in a comfortable and private environment. The Self-Care Interventional Package on the promotion of sexual health was developed in the form of flash book and booklet, and delivered by one-to-one interaction. Three follow-ups were done weekly for motivation in both the groups. Postintervention assessment was conducted after 1 month. Results: There was a statistically significant (P < 0.01) improvement in knowledge about prevention and management of STIs and HIV, getting vaccinated for Hepatitis B and regular self check-up. Statistically significant reduction in unsafe sexual practices was noted among the MSM of experimental group. Conclusion: The self-care interventional package for the promotion of sexual health was effective in improving the sexual heath of the MSM population.